Pengaruh Modul dalam Pembelajaran IPA Terhadap Pengetahuan dan Keterampilan Berpikir Kritis Siswa: Meta Analisis - Asrizal Asrizal; Lidya Jasmi; Nailul Rahmah Pohan; Nurhamdin Putra (Jurnal Penelitian Pendidikan IPA, 2023)
The purpose of this research is to determine the effect of modules in natural science learning on students' knowledge and critical thinking skills. This type of research is meta analysis. The subjects in this study were 20 articles that had been published in various national and international journals. The instrument used is coding. The data analysis method used is quantitative descriptive analysis which is guided by the effect size. After obtaining the effect size value, it is then classified into several groups and adjusted to the effect size category. Based on the results of data analysis, it is known that the average effect size module on knowledge is 1.36 and belongs to the very high category. While the average effect size of the module on students' critical thinking skills is 3.42 and classified in the very high category. The results in this study explain that the module has a very high influence in efforts to increase students' knowledge and critical thinking skills.